2021
DOI: 10.1002/cctc.202100937
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis of Positively Charged Ru Species Stabilized by Hydroxyapatite in Amine Formylation

Abstract: Formamide is an important solvent and synthetic intermediate. Herein, we designed a hydroxyapatite (HAP)‐stabilized, positively charged Ru‐based catalysts which can efficiently catalyze the formylation reaction of amines with CO for the synthesis of formamide. The Ru‐HAP showed excellent catalytic performance in N,N‐Dimethylformamide (DMF) synthesis, with about 75 % dimethylamine conversion and >99 % DMF selectivity at 300 h of continuous reaction. The combination of characterization results and control experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The XRD pattern of HAP was coincided with the typical diffraction peaks ascribed to hydroxyapatite structure (PDF#09-0432). 15,[29][30][31] For Co/HAP(Ce) and HAP(Ce), the diffraction peaks became broader compared with those of Co/HAP and HAP, which indicated that the crystal structures Co/HAP(Ce) and HAP(Ce) were not so regular, an amorphous state existed in some degree. Since CeO 2 (111) and HAP (210) have nearly identical diffraction angles, the diffraction peaks of Co/HAP(Ce) and HAP(Ce) samples at 28.5°m ay be attributed to the presence of CeO 2 (111) (CeO 2 PDF#43-1002) or HAP (210).…”
Section: Characterizationmentioning
confidence: 99%
“…The XRD pattern of HAP was coincided with the typical diffraction peaks ascribed to hydroxyapatite structure (PDF#09-0432). 15,[29][30][31] For Co/HAP(Ce) and HAP(Ce), the diffraction peaks became broader compared with those of Co/HAP and HAP, which indicated that the crystal structures Co/HAP(Ce) and HAP(Ce) were not so regular, an amorphous state existed in some degree. Since CeO 2 (111) and HAP (210) have nearly identical diffraction angles, the diffraction peaks of Co/HAP(Ce) and HAP(Ce) samples at 28.5°m ay be attributed to the presence of CeO 2 (111) (CeO 2 PDF#43-1002) or HAP (210).…”
Section: Characterizationmentioning
confidence: 99%